To solve for g in terms of T and L, we can rearrange the formula as follows:
T = 2π * √(L/g)
First, divide both sides of the equation by 2π:
T / (2π) = √(L/g)
Next, square both sides of the equation to eliminate the square root:
(T / (2π))^2 = L/g
Rearrange the equation to solve for g:
g = L / (T / (2π))^2
Simplifying further:
g = L * (2π/T)^2
Therefore, g in terms of T and L is given by g = L * (2π/T)^2.
The formula to determine the period of one swing of a simple pendulum is T = 2pi * sqrt(L/g) where is the length of the string and g is the acceleration due to gravity. Solve the formula to solve for g in terms of , T and L. pi
1 answer